Предмет:
МатематикаАвтор:
анонимВычислим значение выражения (2/3)^(-2) - (1/9)^(-1) + (6/17)^0 * 1/8 - 0,25^(-2) * 6.
1/(2/3)^2 - 1/(1/9) + 1 * 1/8 - 1/0,25^(2) * 6;
1/(4/9) - 1/(1/9) + 1/8 - 1/(1/4)^(2) * 6;
9/4 - 9/1 + 1/8 - 1/(1/16) * 6;
9/4 - 9/1 + 1/8 - 16 * 6;
9/4 - 9 + 1/8 - 16 * 6 = 9 * 2/(4 * 2) - 9 + 1/8 - 10 * 6 - 6 * 6 = 18/8 + 1/8 - 9 - 60 - 36 = 19/8 - 9 - 60 - 36 = 19/8 - 96 - 9 = 19/8 - 105 = 2,375 - 105 = -102,625;
В итоге получили, (2/3)^(-2) - (1/9)^(-1) + (6/17)^0 * 1/8 - 0,25^(-2) * 6 = -102,625.
Ответ: -102,625.
Автор:
maliapadillaДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть